Cluster Reduction: Deletion or Coalescence? - Max W. Wheeler (Universitat Autònoma de Barcelona, 2005)
I show that a consequence of Correspondence Theory in Optimality Theory is that, for processes such as cluster reduction, if MAX outranks UNIFORMITY, candidates displaying coalescence are preferred to those displaying true deletion. It is thus incumbent on the analyst to identify the constraints that select appropriate coalescence candidates, even for apparent deletion cases. I show how Lamontagne and Rice’s (1995) account of the D-effect in Navajo must be modified to ensure the correct outcome in a language where both coalescence and apparent deletion are repairs to cluster constraint violations. If, for other reasons, it is necessary that UNIFORMITY outrank MAX, the admission of MAX(Feature) constraints becomes unavoidable. An analysis of certain cluster reduction phenomena in Ibiza Catalan shows how complex coda constraints, perceptual markedness constraints for clusters, Paradigm Uniformity, and featural faithfulness interact to derive a pattern of contextual variation. The paper includes a review of Correspondence Theory focusing on its effects in cluster reduction.